DUAL TARGET REVERSE TRANSCRIPTION POLYMERASE CHAIN REACTION FOR SARS-COV-2 FOR ENHANCING ACCURACY WITH E GENE AND ORF1B GENE: A CROSS-SECTIONAL STUDY - GAUTAM BARIK; ISHITA SARKAR; DHIRAJ BISWAS; SANJAYA KUMAR SAHOO (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The pandemic of the recently emerged 2019- novel coronavirus infection was a challenge to public health. The current gold standard for the molecular diagnosis of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection is the reverse transcription polymerase chain reaction (RT-PCR) for the qualitative and quantitative detection of viral nucleic acids. However, superior combination of gene targets for SARS-CoV-2 detection is underexplored. To find out the possible combination of target genes for maximizing RT-PCR accuracy in SARS-CoV-2 detection. Methods: This study is an observational, cross-sectional study conducted at a tertiary care hospital in Kolkata. Study population included all SAR-CoV-2-infected patients attended either inpatient or outpatient department in a tertiary care hospital in eastern India. 870 patient’s respiratory tract samples with the clinical diagnosis of COVID-19 were collected. E gene, N gene, RNA dependent RNA polymerase (RdRp) (open reading frame [ORF1ab]) gene, ORF1b gene, and human RNase P (Internal control) gene targets were detected. Results: Among all the genes, E gene was the most frequently detected (n=665; 86.70%) closely followed by N gene (n=429; 83.30%). ORF1b could be detected in 69.73% (n=159). RdRp was least frequently detected in only 44.64% (n=175). The E gene and ORF1b could simultaneously be detected in 85.12% samples when tested together. E gene and N gene could be detected together in 71.16% and E gene and RdRp could be detected in only 53.41%. Conclusion: Our study found that the combination of E gene and ORF1b gene as optimal targets for assay design as these two genes are expressed simultaneously, that will minimize inconclusive results and maximize diagnostic yield.